Method of processing the results of measurements of medical indicators - Еременко, В. С.; Буриченко, Mихайло Юрійович; Іванець, Ольга Борисівна (Science-based technologies, 2020)
The paper proposes an approach to assessing the state of the human body on the basis of medical indicators with the maximum completeness of obtaining information about the parameters of a given object by measuring physical quantities correlated with this parameter. Significant commonality in the informational relation of the processes of measurement and diagnostics opens up the possibility of their joint research and obtaining ratios that are valid both in diagnostics and control. In both cases, the operation of comparing the results with a given norm is mandatory. In addition, in complex objects there is a statistical relationship between the values of different controlled (measured) quantities, that is, the state of the object. At the same time, control over individual indicators without taking into account possible statistical relationships can lead to erroneous conclusions about the state of the system. To eliminate this drawback, the use of multi-parameter criteria for assessing and diagnosing the stability of complex objects is proposed, in particular, the use of Hotelling T2 statistics for diagnosing the state of complex objects. Possibilities of assessing the stability of multiparametric objects when correlating their indicators using the Hotelling criterion are given. The possibilities of the Hotelling criterion to assess the stability of an object both in stages and in a complex are presented, and to determine indicators and their combinations that significantly affect the stability of the functioning process. The human body was chosen as the object of research by the example of the Antarctic expedition winterers. The use of the proposed processing method increases the reliability of decision-making about the state of the object in comparison with the traditional processing method, which is based on comparison with reference values. Such an increase in reliability is explained by the fact that when carrying out calculations, the comparison of actual values is carried out not with the values of the generally accepted norm, but with the unique norm of each individual subject. Such an approach based on taking into account the individual boundaries of the norm makes it possible to take into account the peculiarities of the individual reaction of each individual organism to the influence of environmental factors. Also, this approach makes it possible to take into account the early (initial) stages of distabilization. The human body was selected as the object of study using the example of wintering workers of the Antarctic expedition. The use of multi-parameter criteria for determining the degradation of a biological object allows not only to conclude that homeostasis is impaired, but also allows researchers to determine exactly which indicators have a significant effect on the degradation of the body system and to take measures to return it to a stable state.